ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI CABAI MERAH (Capsicum annum L.) DI KECAMATAN PANJATAN KABUPATEN KULONPROGO - Dwi Rahayu Ningsih; Ignatius Suprih Sudrajat (Fakultas Pertanian UST, 2018)
This study aims to determine the factors that affect the production of red peppers. This research was conducted in District Panjatan Kulonprogo Regency, precisely in Bugel village. The basic method of research used in this study is the method of observation and survey by conducting interviews directly to the respondents by using questionnaires, then collect and compile data obtained from respoden, and analyze and explain. The method of determining the location is based on the consideration that the district has the largest harvest area and the highest production amount in Kulonprogo Regency, while the sample determination is random sampling.The results showed average land area of 0.26 ha with an average of 16, 8 kw and produktivtas of 65.8 kw / ha. The factors of production of land area, seed, labor, manure, chemical fertilizer, plant spacing, and pesticide together have a real effect on the production of red pepper. Individually seeds have a real effect on the production of red chili, while the area of land, labor, manure, chemical fertilizers, plant spacing and pesticides have no significant effect on the production of red peppers.